The role of cediranib in ovarian cancer: current status and further investigation. (2nd August 2016) - Ethier, Josee-Lyne; Lheureux, Stephanie; Oza, Amit
ABSTRACT: Introduction : Epithelial ovarian cancer (OC) remains a leading cause of cancer death in women. Despite treatment with surgery and chemotherapy, the majority of women will relapse and require additional treatment. Targeted therapies to improve outcomes and prolong survival in the recurrent setting have thus garnered significant interest. Anti-angiogenic agents have led the way in targeted development in OC, and were the first group to have clinical impact. Angiogenesis has been targeted with the use of bevacizumab, a monoclonal antibody directed against VEGF-A, as well as peptibodies, VEGF-Traps, and tyrosine kinase inhibitors (TKI) directed against VEGFR. Cediranib, a TKI directed against VEGFR 1-3 and c-kit, has yielded negative results in large trials for colon and lung cancer. However, recent encouraging results in OC have led to renewed interest in its use. Areas covered : This report reviews the current role of cediranib in OC. Results of completed Phase I, II and III studies are discussed, including trials of cediranib as monotherapy, in combination with olaparib, or given concurrently with chemotherapy followed by maintenance cediranib. Expert opinion : Cediranib showed modest activity as monotherapy in OC, but had a significant interest in combination with olaparib, and clinical benefit in combination with chemotherapy followed by monotherapy maintenance for the treatment of platinum-sensitive recurrent disease. Toxicities induced by cediranib are manageable but require patient and physician education.